2019
DOI: 10.1249/01.mss.0000562132.80624.84
|View full text |Cite
|
Sign up to set email alerts
|

Satiating Effect Of High Protein Diets On Resistance-trained Individuals In Energy Deficit.

Abstract: Short-term energy deficit strategies are practiced by weight class and physique athletes, often involving high protein intakes to maximize satiety and maintain lean mass despite a paucity of research. This study compared the satiating effect of two protein diets on resistance-trained individuals during short-term energy deficit. Following ethical approval, 16 participants (age: 28 ± 2 years; height: 1.72 ± 0.03 m; body-mass: 88.83 ± 5.54 kg; body-fat: 21.85 ± 1.82%) were randomly assigned to 7-days moderate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Macronutrient contribution to total energy intakes are considered factors to be investigated due to the possibility that throughout the course of the intervention, this factor may impact overall energy intake due to gastric emptying variation ( 62 ) or changes in hormonal appetite response ( 63 ) . A macronutrient adjustment intervention was used to impact a variety of factors being investigated: hunger and appetite ( n 5) ( 56 , 57 , 59 61 ) and body composition ( n 2) ( 44 , 58 ) . Studies that included a macronutrient adjustment interventions used a variety of study designs, such as randomised crossover trial ( n 4) ( 44 , 58 , 59 , 61 ) , randomised double-blind trial ( n 1) ( 60 ) , counterbalanced trial ( n 1) ( 57 ) and randomised, double-blind, placebo-controlled trial ( n 1) ( 56 ) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Macronutrient contribution to total energy intakes are considered factors to be investigated due to the possibility that throughout the course of the intervention, this factor may impact overall energy intake due to gastric emptying variation ( 62 ) or changes in hormonal appetite response ( 63 ) . A macronutrient adjustment intervention was used to impact a variety of factors being investigated: hunger and appetite ( n 5) ( 56 , 57 , 59 61 ) and body composition ( n 2) ( 44 , 58 ) . Studies that included a macronutrient adjustment interventions used a variety of study designs, such as randomised crossover trial ( n 4) ( 44 , 58 , 59 , 61 ) , randomised double-blind trial ( n 1) ( 60 ) , counterbalanced trial ( n 1) ( 57 ) and randomised, double-blind, placebo-controlled trial ( n 1) ( 56 ) .…”
Section: Resultsmentioning
confidence: 99%
“…carbohydrate supplementation ( 60 ) . However, Roberts et al ( 61 ) identified significant differences between moderate-protein and high-protein diet groups in ad libitum buffet consumption, with an increase in protein intake and decrease in carbohydrate intake in the high-protein diet intervention group. No significant differences were found in total energy intake for three of the included studies ( 56 58 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations